2020
DOI: 10.1111/ele.13665
|View full text |Cite
|
Sign up to set email alerts
|

When do Janzen–Connell effects matter? A phylogenetic meta‐analysis of conspecific negative distance and density dependence experiments

Abstract: The Janzen–Connell (J‐C) hypothesis suggests that specialised natural enemies cause distance‐ or density‐dependent mortality among host plants and is regarded as an important mechanism for species coexistence. However, there remains debate about whether this phenomenon is widespread and how variation is structured across taxa and life stages. We performed the largest meta‐analysis of experimental studies conducted under natural settings to date. We found little evidence of distance‐dependent or density‐depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 100 publications
(162 reference statements)
3
54
3
1
Order By: Relevance
“…CNDD occurs when a species's mortality rate increases with its density, and this supports diversity and coexistence by limiting local dominance [11]. CNDD can either arise from stronger intraspecific competition than interspecific competition or higher attack rates by plant enemies for common and/or clumped species [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…CNDD occurs when a species's mortality rate increases with its density, and this supports diversity and coexistence by limiting local dominance [11]. CNDD can either arise from stronger intraspecific competition than interspecific competition or higher attack rates by plant enemies for common and/or clumped species [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Differences between our results and previous research 32 may be a product of our inclusion of animal, plant, and cross-kingdom species pairs, as opposed to only plant species pairs, and/or not explicitly estimating the Lotka-Volterra competition coefficients for these competing species 32 . These results also imply that total intraspecific competition pressures may be relatively strong at higher conspecific densities, providing further evidence that the density-dependent mortality observed with Janzen-Connell effects (i.e., greater mortality when conspecifics are aggregated in close proximity) may be, in part, the result of strong intraspecific competition, not just from natural enemies 32,64,65 . To robustly test Janzen-Connell effects, future research should attribute density-dependent mortality to both enemies and intraspecific competition 64 .…”
Section: Discussionmentioning
confidence: 56%
“…These results also imply that total intraspecific competition pressures may be relatively strong at higher conspecific densities, providing further evidence that the density-dependent mortality observed with Janzen-Connell effects (i.e., greater mortality when conspecifics are aggregated in close proximity) may be, in part, the result of strong intraspecific competition, not just from natural enemies 32,64,65 . To robustly test Janzen-Connell effects, future research should attribute density-dependent mortality to both enemies and intraspecific competition 64 . As we found that certain experimental and ecological factors alter the relative strengths of inter-and intra-specific competition, some discrepancies across studies investigating phylogenetic relatedness and functional similarity controls on competition might be the result of differences in predator presence, habitat, relative size of the experimental venue, and relative densities of competing species.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The Janzen-Connell hypothesis suggests that host-specific insect and fungal enemies cause conspecific densitydependent mortality for under-dispersed offspring, which promotes species coexistence and diversity [25][26][27][28] . However, different seed predators cause different spatial patterns of mortality, depending on their mobility and diet specificity 11,28,29 . Importantly, wide-ranging generalist seed predators, such as most vertebrates, are comparatively less important sources of Janzen-Connell effects 11,28,30 .…”
mentioning
confidence: 99%